Effects of roll differential on recycle grinding system in flour milling process: at second break - Mustapa Kamal, Siti Mazlina; Webb, C.; Abdullah, Abdul Ghani Liew (Federation of Engineering Institutions of Islamic Countries, 2006)
One of the key parameters in the flour milling process is roll differential, the relative speeds at which the rolls rotate. The roll differential causes the shearing action on the grain that removes bran from the endosperm. The aim of this study is to evaluate the recycle system at second break with the effects of roll differential. The effects of roll differential on a recycle grinding process in flour milling were investigated using a Satake STR-100 test roller mill. Differentials of each break-roll pair were adjusted to target differentials ratio of 2.0, 2.5, and 3.0 by changing the velocity of the slow roll. Fast rolls were set at a velocity of 550 rpm. Weight percentages for each particle size and ash content from the second break rolls to recycle system were examined. The results show of that changing the roll differential does affect the recycle grinding performance. Roll differential ratio 2.5 had significantly produced higher yield compared to 2.0 and 3.0 roll differential ratio. It was also concluded that the recycle grinding system was successful introduce at break system and could potentially produce the target production without compromising the quality of the finished product.